2011
DOI: 10.1007/s12011-011-9286-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Biological Effect of Nucleotide-Capped CdSe/ZnS Quantum Dots on Tetrahymena thermophila

Abstract: In this paper, we described the preparation and characterization of different types of modified CdSe/ZnS quantum dots (QDs) and explored the biological effects of QDs with different surface modifications on the whole growth of unicellular protozoan Tetrahymena thermophila BF(5) using a thermal activity monitor air isothermal microcalorimeter. Our results demonstrated that adenosine 5'-monophosphate (AMP) showed stronger interaction with QDs than other types of nucleotide. AMP-QDs could stimulate the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…35 In previous research, the population growth rate of P. tricornutum was stimulated when [QDs] # 0.2 nM. 36,37 This effect is also reported in vivo with CdSe/ZnS-QDs and other nanoparticles. However, the effects of CQDs on organisms were less characterized.…”
Section: Analysis Of the Effect On M Aeruginosamentioning
confidence: 61%
“…35 In previous research, the population growth rate of P. tricornutum was stimulated when [QDs] # 0.2 nM. 36,37 This effect is also reported in vivo with CdSe/ZnS-QDs and other nanoparticles. However, the effects of CQDs on organisms were less characterized.…”
Section: Analysis Of the Effect On M Aeruginosamentioning
confidence: 61%
“…The coated CP layer may be further used for entrapping guest molecules and for increasing the colloidal stability of the nanoparticle core. Beyond iron oxide, nucleotides have been used to coat Au nanoparticles, Ag nanoparticles, and semiconductor quantum dots . Datta and co‐workers claimed ATP coated AgNPs for antibacterial studies (Figure D) .…”
Section: Applications Of Nucleotide‐containing Cpsmentioning
confidence: 99%
“…In contrast to SWCNT, the protozoans seemed not to be very sensitive to C 60 fullerene [34], as well as negligible small effect on the proliferation of fullerenol C 60 (OH) x was observed [35]. For nanoparticles used in protozoa studies, successful observation of fluorescent QD inside the ciliate protozoa was demonstrated [30,46]. Iron oxide particles (magnetite) were internalized by Tetrahymena pyriformis and the method which allows control of the swimming direction of an individual cell using the particles magnetizing is discussed [37].…”
Section: Introductionmentioning
confidence: 98%
“…These microorganisms are widely used as model system for study the toxicity of environmental agents; and on the other hand, ciliated protozoa are very well studied and extensively used as a model organism in cell biology, genetics studies, etc. [28][29][30]. Particularly, they are used for phagocytosis and exocytosis studies; protozoa can feed on suspended particles in range of sizes from nm to microns; as result, they are an excellent model organism to the study in situ the biodistribution of the internalized nanoparticles and of their toxic effects at the same time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation